Adolescents with attention deficit hyperactivity disorder and exposure to violence: parents' opinion - Jaqueline Rodrigues Stefanini; Zeyne Alves Pires Scherer; Edson Arthur Scherer; Luciana Aparecida Cavalin; Mariana Santos Guazzelli (Universidade de São Paulo, 2015)
Objective: to identify the opinion of parents or guardians of adolescents diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) about their children's exposure as perpetrators or victims of violence situations in family life or outside. Method: qualitative study with use of thematic oral history. Nine parents of 07 adolescents with ADHD participated. Data were collected from April to September of 2013 using thematic interview. The interviews were recorded at scheduled times at the participants' home, with an average duration of 30 minutes. The findings were submitted to inductive thematic analysis. Results: data analysis allowed the identification of the occurrence of "Conflicts in family life" and "Conflicts in the context of school and community". Parents reported the involvement of their children as victims, perpetrators and witnesses of physical and psychological violence, and the difficulty of them and the school to understand and handle these situations. Conclusion: violence occurs in ADHD adolescents' interpersonal relationships. Communication between health professionals, school and families is precarious. Through the systematization of nursing care, nurses can plan strategies that articulate support networks and interpersonal relationships of adolescents with the disorder (family and school).